ANALISIS KINERJA UNIT LAYANAAN DISABILITAS KETENAGAKERJAAN DALAM MENINGKATKAN SERAPAN TENAGA KERJA PENYANDANG DISABILITAS DI KOTA SEMARANG - Arga Kusumo Hartono; Amni Zarkasyi Rahman (Journal of Management and Public Policy, 2026)
Fulfillment of employment is a very important socio-economic problem, especially for people with disabilities. The Semarang City Government, through the Employment Disability Services Unit, in its implementation experiences complexity in the absorption of disabled workers, where the number of disabled people of productive age is not proportional to the level of job placement, indicating problems in the performance of the Employment Disability Services Unit (ULD). This study aims to analyze the performance of the Semarang City Employment Disability Services Unit in increasing the absorption of disabled workers and identify factors that influence its implementation. The theoretical study uses the concept of public sector organizational performance from Agus Dwiyanto which includes productivity, service quality, and responsiveness, as well as the theory of factors that influence organizational performance according to Soesilo (2014), namely organizational structure, management policies, human resources, management information systems, and facilities and infrastructure. This study uses a qualitative approach with descriptive methods with data collection techniques through interviews, observation, and documentation. Data analysis is carried out through data collection, data condensation, data presentation, conclusions, and data verification with source triangulation. The research results indicate that the performance of the Employment Unit (ULD) is suboptimal, particularly in terms of productivity, service quality, and responsiveness due to limited human resources, an unintegrated information system, and a lack of strategic partnerships with the business sector. Strengthening the performance of the Semarang City Disability Services Unit (ULD) for Employment is essential by increasing the productivity of its job placement program, improving the quality of inclusive services, and enhancing the organization's responsiveness to the needs of people with disabilities. Furthermore, strengthening organizational factors and strategic collaboration with the business sector are crucial steps in encouraging increased employment of people with disabilities in Semarang.